(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe patient satisfaction at the Examination Department of Thanh Hoa Provincial Oncology Hospital in 2024 and identify factors associated with satisfaction. Methods: A cross-sectional descriptive study was conducted with 126 patients visiting the Examination Department of Thanh Hoa Provincial Oncology Hospital in 2024, who voluntarily participated. Result: Of the 126 patients, 13.5% were male and 86.5% were female. The overall satisfaction rate was 92.5%, with the highest satisfaction for facilities and equipment (94.1%) and the lowest for service delivery outcomes (90.7%). Age, gender, and health insurance use were not found to be associated with satisfaction. Education level influenced satisfaction with facilities, waiting time for registration, and staff attitude; patients with high school education have higher reported lower satisfaction (80.4%, 83.9%, and 89.3%, respectively) compared to those with less than high school education (100%, 97.1%, and 100%), with p < 0.001 and p < 0.05. Marital status was associated with satisfaction regarding waiting time for registration; married or widowed patients had lower satisfaction (33.33%) compared to single or married patients (100% and 92.50%), with p < 0.05. Conclusion: Most patients were satisfied with the services at Thanh Hoa Provincial Oncology Hospital. However, some dissatisfaction persists, influenced by education level and marital status. Continuous improvements are needed to enhance satisfaction for all patients.